Dietary switch reveals fast coordinated gene expression changes in Drosophila melanogaster - Whitaker, Rachel (Impact Journals LLC, 2014)
Dietary restriction (DR) reduces age-specific mortality and increases lifespan in many organisms. DR elicits a large number of physiological changes, however many are undoubtedly not related to longevity. Whole-genome gene expression studies have typically revealed hundreds to thousands of differentially expressed genes in response to DR, and a key open question is which subset of genes mediates longevity. Here we performed transcriptional profiling of fruit flies in a closely spaced time series immediately following a switch to the DR regime and identified four patterns of transcriptional dynamics. Most informatively we find 144 genes rapidly switched to the same level observed in the DR cohort and are hence strong candidates as proximal mediators of reduced mortality upon DR. This class was enriched for genes involved in carbohydrate and fatty acid metabolism. Folate biosynthesis was the only pathway enriched for gene up-regulated upon DR. Four among the down-regulated genes are involved in key regulatory steps within the pentose phosphate pathway, which has been previously associated with lifespan extension in Drosophila. Combined analysis of dietary switch with whole-genome time-course profiling can identify transcriptional responses that are closely associated with and perhaps causal to longevity assurance conferred by dietary restriction.